PENGEMBANGAN MEDIA AJAR BERBASIS VIDEO ANIMASI DALAM MENINGKATKAN PEMAHAMAN KONSEP PADA PEMBELAJARAN IPAS DI KELAS IV SD NEGRI 61 BANDA ACEH - Rizki Juanda; Lili Kasmini; Haris Munandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Most teachers are still lacking in utilizing learning media in the form of animated videos because they find it difficult to utilize technology in learning. This study aims to develop animated video-based teaching media to improve students' conceptual understanding in science learning on changing energy forms in grade IV of SD Negeri 61 Banda Aceh. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were grade IV students of SD Negeri 61 Banda Aceh. Data collection techniques were carried out through observation, expert validation questionnaires, and pretest and posttest tests. The results of the study showed that the developed animated video-based teaching media obtained validation scores from material experts of 88%, language experts of 88%, and media experts of 94% with a very valid category. Then, the test results showed an increase in students' conceptual understanding as seen from the average pretest score of 55.6 increasing to 93.6 in the posttest. Thus, animated video-based teaching media is very suitable for use to improve students' conceptual understanding in science learning